Opium as a risk factor for early-onset coronary artery disease: Results from the Milano-Iran (MIran) study. - Alberto Maino; Saeed Sadeghian; Ilaria Mancini; Seyed Hesameddin Abbasi; Hamidreza Poorhosseini; Mohammad Ali Boroumand; Masoumeh Lotfi-Tokaldany; Arash Jalali; Maria Teresa Pagliari; Frits R Rosendaal; Flora Peyvandi (PLoS ONE, 2023)
The spreading of opium use poses new health related concerns. In some areas of Asia its use is believed to protect from cardiovascular disorders, such as coronary artery disease (CAD). However, whether opium use has an association with CAD is unclear. We aimed to investigate the association between non-medical opium use and CAD. We set up a case-control analysis, i.e., the Milano-Iran (MIran) study by enrolling consecutive young patients who underwent a coronary angiography at the Tehran Heart Center, between 2004 and 2011. Incident cases with CAD were contrasted with controls for opium use. Relative risks were calculated in terms of odds ratios (ORs) by logistic regression models adjusted for age, sex, cigarette smoking, body mass index, hypertension, hyperlipidaemia, and diabetes. Interaction analyses were performed between opium and major cardiovascular risk factors. 1011 patients with CAD (mean age 43.6 years) and 2002 controls (mean age 54.3 years) were included in the study. Habitual opium users had a 3.8-fold increased risk of CAD (95%CI 2.4-6.2) compared with non-users. The association was strongest for men, with a fully adjusted OR of 5.5 (95%CI 3.0-9.9). No interaction was observed for the combination of opium addiction and hypertension, or diabetes, but an excess in risk was found in opium users with hyperlipidaemia (OR 16.8, 95%CI 8.9-31.7, expected OR 12.2), suggesting supra-additive interaction. In conclusion, despite common beliefs, we showed that non-medical opium use is associated with an increased risk of CAD, even when other cardiovascular risk factors are taken into account.